Inovasi Soft Cookies Berbahan Tepung Mocaf dengan Perbedaan Jumlah Margarin dan Mentega - Aprilianti, Ovi; Sulandari, Lilis; Pangesthi, Lucia Tri; Dewi, Ila Huda Puspita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Soft cookies made from mocaf flour with varying amounts of margarine and butter are baked products composed of mocaf flour, cocoa powder, margarine, butter, eggs, powdered sugar, and chocolate chips. This study aims to examine the effect of different margarine and butter proportions on the sensory attributes of soft cookies, including shape, color, aroma, taste, texture, and overall preference. It also includes a nutritional analysis of the best formulation. This experimental study used variations of margarine and butter (40%, 45%, and 50% of the total dry ingredients) as the independent variable. Data were collected through sensory evaluation involving 35 panelists (4 trained and 31 semi-trained). Data analysis employed one-way ANOVA followed by Duncan’s multiple range test. The results showed significant differences in shape, aroma, taste, texture, and overall preference among the soft cookies with different margarine and butter ratios. The best soft cookie formulation—containing 50% margarine and butter—had the following nutritional values: carbohydrates 70.10%, fat 6.08%, protein 7.90%, moisture 11.80%, and fiber 2.98%.